Shelf-life of tail meat of the giant river prawn, Macrobrachium rosenbergii, stored on ice - Kirschnik, Peter Gaberz [UNESP]; Viegas, Elisabete Maria Macedo [UNESP]; Valenti, Wagner Cotroni [UNESP]; De Oliveira, Carlos Augusto Fernandes [UNESP] (Taylor & Francis, 2006)
The objective of this study was to evaluate the shelf-life of peeled giant river prawn Macrobrachium rosenbergii stored directly in contact with ice (DCI), and without direct contact with ice (WCI). The prawns from DCI treatment showed an intense leaching of non-protein nitrogen (NPN) and total volatile bases nitrogen (TVB-N), thus suggesting that NPN or TVB-N should not be used as freshness indicators of peeled tails stored directly in contact with ice. Loss of flavor and a quick texture tactile decrease with time occurred in both treatments. The shelf-life of peeled tails prepared from M. rosenbergii was 7 days for DCI and 10 days WCI. © 2006 by The Haworth Press, Inc. All rights reserved.
Keywords: Macrobrachium rosenbergii; NPN; Shelf life; Storage on ice; TVB-N